A Counter Propagating Lens‐Mirror System for Ultrahigh Throughput Single Droplet Detection. Issue 20 (20th April 2020) - Cao, Xiaobao; Du, Ying; Küffner, Andreas; Van Wyk, Jordan; Arosio, Paolo; Wang, Jing; Fischer, Peter; Stavrakis, Stavros; deMello, Andrew
Abstract: Fluorescence‐based detection schemes provide for multiparameter analysis in a broad range of applications in the chemical and biological sciences. Toward the realization of fully portable analysis systems, microfluidic devices integrating diverse functional components have been implemented in a range of out‐of‐lab environments. That said, there still exits an unmet and recognized need for miniaturized, low‐cost, and sensitive optical detection systems, which provide not only for efficient molecular excitation, but also enhanced photon collection capabilities. To this end, an optofluidic platform that is adept at enhancing fluorescence light collection from microfluidic channels is presented. The central component of the detection module is a monolithic parabolic mirror located directly above the microfluidic channel, which acts to enhance the number of emitted photons reflected toward the detector. In addition, two‐photon polymerization is used to print a microscale‐lens below the microfluidic flow channel and directly opposite the mirror, to enhance the delivery of excitation radiation into the channel. Using such an approach, it is demonstrated that fluorescence signals can be enhanced by over two orders of magnitude, with component parallelization enabling the detection of pL‐volume droplets at rates up to 40 000 droplets per second. Abstract : A counter propagating lens‐mirror microarray is embedded within a large field of view microfluidic platform for enhanced excitation and photon collection efficiency equivalent to that of high numerical aperture objectives